Corporate societal marketing: Beyond traditional benevolent philanthropy - Divinagracia, Louie A. (Animo Repository, 2004)
The author examines consumer perceptions as a function of a company’s corporate societal marketing (CSM) efforts, the consumer’s knowledge of the firm’s CSM activities and the factors perceived to be driving these initiatives. Employing survey research, the study involves a purposive sample of 150 business students and 150 owner-managers of small family businesses, with a leading food corporation as the target company. Results show that the consumers’ knowledge of a company’s CSM activities and the perceived factors driving these activities jointly influence the consumers’ meaningful associations about the company’s product-CSM activity mix. These associations further influence the consumers’ performance evaluation of the company’s CSM initiatives, implying that the organization’s marketing concept should include social responsibility as a primary function.